Localization of Fibrinolytic Activators and Inhibitors in Normal and Atherosclerotic Vessels - Fålkenberg, Marten; Tjärnstrom, Johan; Örtenwall, Per; Olausson, Michael; Risberg, Bo (Thrombosis and Haemostasis, 1996)
Local fibrinolytic changes in atherosclerotic arteries have been suggested to influence plaque growth and promote mural thrombosis on ruptured or ulcerated plaques. Increased levels of plasminogen activator inhibitor (PAI-1) have been found in atherosclerotic arteries. In this study tissue plasminogen activator (t-PA), urokinase-type plasminogen activator (u-PA) and PAI-1 were localized in arterial biopsies of healthy and atherosclerotic vessels by immunohistochemis-try. The expression of fibrinolytic regulators was related to the distribution of endothelial cells (EC) and macrophages. Results: t-PA was expressed in vasa vasorum. PAI-1 was positive in endothelial cells, in the media and in the adventitia. Increased expression of t-PA, u-PA and PAI-1 was found in atherosclerotic vessels. t-PA, u-PA, PAI-1 and macrophages were co-localized in plaques. These results support the concept that macrophages can be important in the local regulation of fibrinolysis in atherosclerotic vessels.